Age of vice eaudiobook A novel. - Kapoor, Deepti (Penguin Audio, 2023)
AN INSTANT NEW YORK TIMES BESTSELLER A GOOD MORNING AMERICA BOOK CLUB PICK Named a Best Book of the Year by Publishers Weekly, Oprah Daily and NPR! “Dazzling...Finally free from the book’s grip, now all I want to do is get others hooked.”— The Washington Post “A page-turning social novel…It stirs the pulse while digging into the entrenched and evolving structures and contradictions of modern India.” —NPR “Cinematic…As a storyteller, Kapoor is a natural.” — The New York Times   New Delhi, 3 a.m. A speeding Mercedes jumps the curb and in the blink of an eye, five people are dead. It’s a rich man’s car, but when the dust settles there is no rich man at all, just a shell-shocked servant who cannot explain the strange series of events that led to this crime. Nor can he foresee the dark drama that is about to unfold. Deftly shifting through time and perspective in contemporary India, Age of Vice is an epic, action-packed story propelled by the seductive wealth, startling corruption, and bloodthirsty violence of the Wadia family — loved by some, loathed by others, feared by all. In the shadow of lavish estates, extravagant parties, predatory business deals and calculated political influence, three lives become dangerously intertwined: Ajay is the watchful servant, born into poverty, who rises through the family’s ranks. Sunny is the playboy heir who dreams of outshining his father, whatever the cost. And Neda is the curious journalist caught between morality and desire. Against a sweeping plot fueled by loss, pleasure, greed, yearning, violence and revenge, will these characters’ connections become a path to escape, or a trigger of further destruction?  Equal parts crime thriller and family saga, transporting readers from the dusty villages of Uttar Pradesh to the urban energy of New Delhi, Age of Vice is an intoxicating novel of gangsters and lovers, false friendships, forbidden romance, and the consequences of corruption. It is binge-worthy entertainment at its literary best.